Rapid unimolecular reaction of stabilized Criegee intermediates and implications for atmospheric chemistry - Long, Bo (Nat Commun, 2019)
Elucidating atmospheric oxidation mechanisms is necessary for estimating the lifetimes of atmospheric species and understanding secondary organic aerosol formation and atmospheric oxidation capacity. We report an unexpectedly fast mechanistic pathway for the unimolecular reactions of large stabilized Criegee intermediates, which involves the formation of bicyclic structures from large Criegee intermediates containing an aldehyde group. The barrier heights of the mechanistic pathways are unexpectedly low – about 2–3 kcal/mol – and are at least 10 kcal/mol lower than those of hydrogen shift processes in large syn Criegee intermediates; and the calculated rate constants show that the mechanistic pathways are 10(5)-10(9) times faster than those of the corresponding hydrogen shift processes. The present findings indicate that analogous low-energy pathways can now also be expected in other large Criegee intermediates and that oxidative capacity of some Criegee intermediates is smaller than would be predicted by existing models.